2022
DOI: 10.3389/fpubh.2022.953850
|View full text |Cite
|
Sign up to set email alerts
|

Targeting COVID-19 vaccine hesitancy among nurses in Shanghai: A latent profile analysis

Abstract: ObjectivesThis study aims to clarify the profiles of the psychological antecedents of vaccine hesitancy among Shanghai nurses with a person-centered approach.MethodsA population-based cross-sectional online survey was conducted on Shanghai nurses from July to August 2021 (N = 1,928). In the online survey, participants were asked to report their sociodemographic, the 5C vaccine hesitancy components, their knowledge level of COVID-19 vaccine and vaccination, and the COVID-19 vaccination uptake intention and atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
(64 reference statements)
3
3
0
Order By: Relevance
“…However, despite this assumption, our results suggest that high calculation is not an exclusive characteristic of believers. The second profile was the middler, characterized by about average levels of all 5C components and was partially in line with the previous literature [ 23 , 25 ]. More specifically, we found that this profile showed a configuration of the 5Cs that are not extreme in their values, with true means above 5 (agree point on the response scale) for calculation and confidence, and 6 for collective responsibility.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…However, despite this assumption, our results suggest that high calculation is not an exclusive characteristic of believers. The second profile was the middler, characterized by about average levels of all 5C components and was partially in line with the previous literature [ 23 , 25 ]. More specifically, we found that this profile showed a configuration of the 5Cs that are not extreme in their values, with true means above 5 (agree point on the response scale) for calculation and confidence, and 6 for collective responsibility.…”
Section: Discussionsupporting
confidence: 90%
“…Taking a person-centered approach, we empirically identified four different profiles of HCWs based on their scores in 5Cs measure [ 14 ]. The majority of our population of HCWs falls into the believer profile, converging with results from previous research, defined by the highest levels of confidence and collective responsibility, and lowest levels in complacency and constraints [ 23 , 25 , 27 ]. Furthermore, in line with Zhang and colleagues [ 25 ], in our study, calculation was slightly below average levels, and it was the profile with the lowest levels of calculation.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations